2022
DOI: 10.3390/ijms23063170
|View full text |Cite
|
Sign up to set email alerts
|

Knee and Peri-Knee Tissues of Post Mortem Donors Are Strategic Sources of Mesenchymal Stem/Stromal Cells for Regenerative Procedures

Abstract: Tissues of post mortem donors represent valuable alternative sources for the isolation of primary cells with mesenchymal stem/stromal cell (MSC)-like properties. However, the properties of primary cells derived from different tissues and at different post mortem times are poorly recognized. Here, we aim to identify the optimal tissue source between three knee and peri-knee tissues for the isolation of primary cells with MSC-like properties, and to define the influence of the time post mortem on the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…p values < 0.05 were considered as statistically significant. A heat map was generated, as described previously [16,17] using the online Heatmapper software [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…p values < 0.05 were considered as statistically significant. A heat map was generated, as described previously [16,17] using the online Heatmapper software [24].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, quantitative polymerase chain reaction (qPCR) was performed using 5× HOT FIREPol EvaGreen qPCR Supermix (Solis BioDyne), according to manufacturer protocol. The sequences of the primers (Macrogen, Sigma-Aldrich) used to measure genes encoding hSSC markers and osteogenesis-and adipogenesis-related genes were used from our [17], and other, previous studies [18][19][20][21]. All qPCR experiments were performed in triplicates, using a LightCycler 480 II (Roche).…”
Section: Rna Isolation Reverse Transcription and Gene Expression Prof...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tissues from postmortem donors were also proposed as valuable alternative sources for the isolation of primary cells with MSC-like properties [ 19 , 20 ]. Haring et al reported the identification of an optimal tissue source among three knee and peri-knee tissues for the isolation of primary cells with MSC-like properties, and described the effect of the postmortem time on the properties of these cells [ 21 ]. In fact, the success rate of primary cell isolation depends on the postmortem time.…”
mentioning
confidence: 99%